River channel stability assessment under flow alteration: The Brda River case study (Poland) - Dawid Szatten; Alberto Bosino (Acta Universitatis Carolinae Geographica)
The processes of erosion, transport, and accumulation of river sediments are determined by the balance between the natural fluvial processes and the anthropic pressure. Evaluation of the degree of river channel stability is one of the ways to establish the pressure of human activity that could be directly reflected in the volume of eroded or accumulated sediments in a river. The research here proposed is focused on the last natural section of the Brda River (Poland), which represents a natural hotspot in a deeply anthropized fluvial system. To evaluate the human pressure on the natural river section, we developed a methodology that integrates hydrological and sedimentological studies as well as remotely sensed data. In particular, we applied: (i) the Indicators of Hydrologic Alteration (IHA) method, based on hydrological data; (ii) the erosion coefficient, based on suspended sediment balance; and (iii) spatial analyses of riverbed centerline migration of the Brda River in the section from Woziwoda to Płaskosz (northern Poland) to gain a comprehensive understanding of the fluvial dynamics in the area over a period of 60 years. A significant peculiarity of this research refers to the year 2001 when the operational regime of the Mylof Reservoir was changed from hydropeaking to run-of-river. The results obtained indicate a minor river regime transformation and sediment transport continuum disturbance. Finally, the link between the stability of the Brda riverbed, and the intensification of bank erosion (meandering) resulting from the balance of sediment supply, has been demonstrated. The results presented reflect the climate change trends (on the macro-scale) and human activity in the catchment (on the micro-scale) on the fluvial processes.